2018
DOI: 10.1371/journal.pone.0202817
|View full text |Cite
|
Sign up to set email alerts
|

Formative evaluation of a training intervention for community health workers in South Africa: A before and after study

Abstract: BackgroundCommunity Health Workers (CHWs) have a crucial role in improving health in their communities and their role is being expanded in many parts of the world. However, the effectiveness of CHWs is limited by poor training and the education of CHWs has received little scientific attention.MethodsOur study was carried out in two districts of KwaZulu-Natal, South Africa. We developed and piloted an inexpensive (two day) training intervention covering national government priorities: HIV/AIDS, sexually transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Training can be an intervention choice to increase knowledge and with training it can increase the confidence of officers to provide advice to people at risk of HIV. Training programs for cadre need to be improved because it will have an impact on increasing cadre knowledge [28] According to [16] interventions especially interventions that help improve HIV / AIDS knowledge among students, positively changing students' attitudes towards HIV / AIDS. However, the data from table 3.2 shows that 1 person has less knowledge after being given intervention, this is due to several factors that can influence people's knowledge, such as education level.…”
Section: Resultsmentioning
confidence: 99%
“…Training can be an intervention choice to increase knowledge and with training it can increase the confidence of officers to provide advice to people at risk of HIV. Training programs for cadre need to be improved because it will have an impact on increasing cadre knowledge [28] According to [16] interventions especially interventions that help improve HIV / AIDS knowledge among students, positively changing students' attitudes towards HIV / AIDS. However, the data from table 3.2 shows that 1 person has less knowledge after being given intervention, this is due to several factors that can influence people's knowledge, such as education level.…”
Section: Resultsmentioning
confidence: 99%
“…It differs from the result of another study that employed training intervention to CHWs by using a module in reproductive health and Tuberculosis elds, which demonstrated that there was a large effect. Even though the elds are different, the idea of emphasizing the con dence and satisfaction of CHWs proposed by the study remains essential and relevant (43). In the future, it is suggested to improve the training by emphasizing such insight as well as considering different measures to reach a larger effect in 6 to 12 months (44).…”
Section: Discussionmentioning
confidence: 99%
“…However, no intervention was given in the research. The interview result showed that the cadres often gathered and created bigger study groups to learn together (43). In further action research, quantitative research can be performed to objectively evaluate video education that is embedded as part of the mobile app.…”
Section: Discussionmentioning
confidence: 99%
“…It differs from the result of another study that employed training intervention to CHWs by using a module in reproductive health and Tuberculosis elds which demonstrated that there was a large effect. Even though the elds are different, the idea of emphasizing the con dence and satisfaction of CHWs proposed by the study remains essential and relevant (42). In future, it is suggested to improve the training by empasizing such insight as well as considering different measures to reach a larger effect in 6 to 12 months (43).…”
mentioning
confidence: 99%
“…However, no intervention was given in the research. The interview result showed that the cadres often gathered and created bigger study groups in order to learn together (42). In the further action research, the quantitative research can be performed to objectively evaluate video education that is embedded as part of the mobile app.…”
mentioning
confidence: 99%